Chromosome doubling in Cattleya tigrina A. Rich - Menezes-Sá, Thays Saynara Alves; Arrigoni-Blank, Maria de Fátima; Santos da Costa, Andréa; Santos-Serejo, Janay de Almeida; Fitzgerald Blank, Arie; Alves Soares, Caroline; Santos Moura, Giulia Millena (Scientia Plena, 2019)
Chromosome doubling induction in orchids may benefit their production for resulting in flowers of higher commercial value, larger size and higher content of substances that intensify the color and fragrance when compared with diploid orchids. This work aimed to induce and confirm artificial polyploidization, using flow cytometry and stomatal analysis. Explants were treated with colchicine at concentrations of 0, 2.5, 7.5, and 12.5 mM, for 24 and 48 hours and with oryzalin, at concentrations of 0, 10, 30, and 50 μM, for three and six days. For the flow cytometric analysis, a sample of leaf tissue was removed from each plant, crushed to release the nuclei and stained with propidium iodide. In addition to flow cytometry, the ploidy of the antimitotic treated plants was evaluated by stomata analysis. Young leaves were used where the density, functionality and stomatal index were evaluated. Colchicine provided induction of satisfactory polyploidy in C. tigrina at all concentrations and times of exposure, obtaining a greater number of polyploid individuals in the concentration of 12.5 mM for 48 hours. Oryzalin did not induce chromosome duplication at the tested concentrations.